A Companion to the History of the English Language. - Momma, Haruko (Blackwell companions to literature and culture., 2008)
A Companion to the History of the English Language addresses the linguistic, cultural, social, and literary approaches to language study. The first text to offer a complete survey of the field, this volume provides the most up-to-date insights of leading international scholars.: An accessible reference to the history of the English language; Comprises more than sixty essays written by leading international scholars; Aids literature students in incorporating language study into their work; Includes an historical survey of the English language, from its Germanic and Indo- European beginnings to.